2008
DOI: 10.1111/j.1743-6109.2008.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and its Association with Genitourinary Disorders in Men Undergoing Prostate Cancer Screening

Abstract: Introduction Elevated body mass index (BMI) may predispose to several pelvic pathologies. Aims We tested the association between BMI and five end points, namely, (i) erectile dysfunction (ED); (ii) lower urinary tract symptoms (LUTS); (iii) chronic prostatitis-associated pain (CPP); and ejaculatory dysfunction that is subdivided between (iv) pain/discomfort on ejaculation; and (v) subjectively decreased ejaculate volume. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Likewise, it was a significant (P < 0.019) independent risk factor for ED. These findings could have been confirmed by Bhojani et al who reported that men with major depression were 5.8 times more likely to report poor or very poor erections [28]. If ED is responsible for depression or the other way around remains unclear.…”
Section: Ed and Comorbiditiessupporting
confidence: 54%
“…Likewise, it was a significant (P < 0.019) independent risk factor for ED. These findings could have been confirmed by Bhojani et al who reported that men with major depression were 5.8 times more likely to report poor or very poor erections [28]. If ED is responsible for depression or the other way around remains unclear.…”
Section: Ed and Comorbiditiessupporting
confidence: 54%
“…1214 However, studies that investigated categories of overweight and obesity in relation to self-reported history of prostatitis showed protective findings 7,9 and those that examined overweight/obesity in relation to CP/CPPS or pain/discomfort with ejaculation showed mixed findings. 10,11,15 While reasons for these conflicting results are unclear, each of these studies was cross-sectional and several were small with minimal to no adjustment for covariates associated with metabolism or weight, such as physical activity, diet and smoking. In our large cohort study we observed no association between obesity and CP/CPPS risk before and after adjusting for other lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…Camps et al (1996) revealed that weight loss, that is attained through bariatric surgery, improves body image and sexuality, which are directly related to mood stability and inversely connected to depression. Bhojani et al (2008) reported that men with major depression were 5.8 times more likely to report poor or very poor erections. If ED is responsible for depression or the other way around remains unclear.…”
Section: Discussionmentioning
confidence: 99%